Fast food survival guide - Learning seed (Lake Zurich, III : Learning Seed, 2005)
Fast food survival guide shows how fast food can be part of a healthy diet . It explores the problem with fast food without labelling it all as' junk food'
Keywords: Convenience foods; Food habits; Food -- Caloric content; Food -- Analysis